Perception from population about noise produced by public transport in district of Barranca, Lima, Peru - Castillo Corzo, Miguel A. (2020)
The present study shows the results of the research carried out on the perception of the inhabitants of the Barranca district in Lima, Peru, regarding the influence of environmental noise produced by vehicular transport. As a methodology to collect information, a survey was applied, with which it was confirmed if people considered that vehicular noise affected their daily work and then, to those who responded positively, the instrument was applied with five questions and four levels of response. The results were treated with descriptive statistics (frequency analysis) and inferential statistics (Friedman's Variance) to establish the degree of relevance of each factor. It was obtained that the majority considers that vehicle noise does not affect (58.2%) and that those who consider that it does affect place lack of concentration as the most important problem, followed by stress and aggressiveness. There is a significant difference between the results of the questions with a 95% confidence level. Likewise, the questions were placed in three groups according to the Friedman test (bad mood and hearing loss, stress and aggressiveness, concentration), which present statistical equality within groups and differences outside groups.